Meloxicam, an inhibitor of cyclooxygenase-2, increases the level of serum G-CSF and might be usable as an auxiliary means in G-CSF therapy - Hofer, M; Pospíšil, M; Znojil, V; Holá, J; Vacek, A; Štreitová, D (Physiological research, 2008)
Hematopoiesis-modulating action of meloxicam, a cyclooxyge-nase-2 inhibitor, has been evaluated in mice. Increased serum level of granulocyte colony-stimulating factor (G-CSF) after meloxicam administration has been found in sublethally gamma-irradiated animals. In further experiments hematopoiesis-stimulating effects of meloxicam and G-CSF given alone or in combination have been investigated. Granulocyte/macrophage progenitor cells counts were used to monitor these effects. Meloxicam and exogenous G-CSF did not act synergistically when given in combination, but could be mutually substituted during their repeated administration. The results suggest a promising possibility of using meloxicam as an auxiliary drug reducing the high costs of G-CSF therapy of myelosuppression.
Keywords: buněčná diferenciace; Thiazines; Bone Marrow; leukopenie; lékové interakce; Hematopoiesis; Leukopenia; inhibitory cyklooxygenasy 2; zvířata; myši; Whole-Body Irradiation; faktor stimulující kolonie granulocytů; Mice; Drug Interactions; hematopoéza; Mice, Inbred CBA; Cyclooxygenase 2 Inhibitors; thiazoly; granulocyty; Male; thiaziny; celotělové ozáření; meloxikam; Cell Differentiation; kostní dřeň; Granulocytes; Granulocyte Colony-Stimulating Factor; Meloxicam; Thiazoles; Animals; myši inbrední CBA; mužské pohlaví; kombinovaná farmakoterapie; Drug Therapy, Combination